On Lamb waves in the system: an ideal fluid layer – an elastic layer - Bahno, O.M. (Reports of the National Academy of Sciences of Ukraine, 2015)
Basing on the three-dimensional linear equations of the classical theory of elasticity for a solid and on the linearized Euler equations for a fluid, the propagation of Lamb waves in an elastic layer that interacts with the layer of an ideal compressible fluid is studied. For the normal waves, the dispersion curves in a wide range of frequencies are constructed. The effect of the fluid layer thickness on the dispersion of the phase velocities of Lamb modes in a hydroelastic waveguide is analyzed for both thin and thick fluid and elastic layers.